Clobazam higher-evening differential dosing as an add-on therapy in refractory epilepsy. (August 2016) - Thome-Souza, Sigride; Klehm, Jacquelyn; Jackson, Michele; Kadish, Navah E.; Manganaro, Sheryl; Fernández, Iván Sánchez; Loddenkemper, Tobias
Highlights: Clobazam differential dosing study according to circadian seizure pattern. Differential dosing improved seizure frequency in predominantly nighttime seizures. Generalized seizures benefitted more from differential dosing of clobazam. Abstract: Purpose: Clobazam treatment tailored to the timing of patient's seizures may improve seizure control. We aim to describe the safety and efficacy of higher-evening differential dose of clobazam as add-on therapy in patients with night-time/early morning seizures. Method: Differential dosing with higher evening dosing was started based on a high proportion of seizures (>80%) at nighttime (6 p.m. to 6 a.m.). Differential dosing was defined as providing more than 50% of the total daily dose of clobazam after 6 p.m. Results: Twenty-seven patients were treated with clobazam differential dosing as an add-on therapy. The median age was 9.1 years, with 11 (40.7%) females and median of the first follow-up was 2.7 months. Patients with differential dosing tolerated a higher median total clobazam dose of 0.8 mg/kg/d at first follow-up, as compared to 0.6 mg/kg/d in controls. In differential dose, the median percentage of the total clobazam dose administered in the evening was 66.7%. Differential dose patients exhibited a median seizure reduction of 75% as compared to 50% in controls ( p < 0.005). Patients with generalized seizures benefited the most from differential dosing with a 77.5% median seizure reduction, as compared to 50% in controls ( p = 0.017). Conclusion: Higher-evening differential dose of clobazam improved seizure control in patients with predominantly nighttime and early-morning seizures. Chronotherapy tailored to the patients' seizure susceptibility patterns may improve care in epilepsy patients as differential dosing may allow for higher overall treatment doses at times of greatest seizure susceptibility without increased side effects at other times.